Bifidobacterium jacchi sp. nov., isolated from the faeces of a baby common marmoset (Callithrix jacchus) - Modesto, Monica; Watanabe, Koichi; Arita, Masanori; Satti, Maria; Oki, Kaihei; Sciavilla, Piero; Patavino, Claudio; Cammà, Cesare; Michelini, Samanta; Sgorbati, Barbara; Mattarelli, Paola (International journal of systematic and evolutionary microbiology, 2019)
A novel Bifidobacterium strain, MRM 9.3 , was isolated from a faecal sample of a baby common marmoset (Callithrixjacchus). Cells were Gram-stain-positive, non-motile, non-sporulating, non-haemolytic, facultatively anaerobic and fructose 6-phosphate phosphoketolase-positive. Phylogenetic analyses based on 16S rRNA genes as well as multilocus sequences (representing hsp60, rpoB, clpC, dnaJ and dnaG genes) and the core genomes revealed that strain MRM 9.3 exhibited phylogenetic relatedness to Bifidobacterium myosotis DSM 100196 . Comparative analysis of 16S rRNA gene sequences confirmed the phylogenetic results showing the highest gene sequence identity with strain B.ifidobacterium myosotis DSM 100196 (95.6 %). The average nucleotide identity, amino acid average identity and in silico DNA-DNA hybridization values between MRM 9.3 and DSM 100196 were 79.9, 72.1 and 28.5 %, respectively. Phenotypic and genotypic features clearly showed that the strain MRM 9.3 represents a novel species, for which the name Bifidobacterium jacchi sp. nov. is proposed. The type strain is MRM 9.3 (=DSM 103362 =JCM 31788 ).